A Study Portable Tea Set Based on the Application of Huizhou Design Elements in China - Shi, Yongkang; Han, Sangyun (Journal of Ecohumanism, 2025)
The continuous advancement of science and technology and the constant evolution of product forms have been driving changes in product design. Therefore, contemporary product design must go beyond functional development, aiming for higher performance and broader market coverage. Portable product design is adapting to the changing market demands. In the case of portable tea sets, the industry is advocating for higher design standards through new conceptual approaches. Since Huizhou culture and tea culture hold significant positions in Chinese culture, this paper applies Huizhou cultural elements to the design of portable tea sets, using them as a medium for cultural dissemination. By using Huizhou’s horse-head walls and the "Three Carvings" (wood, brick, and stone carvings) as symbolic elements, their shapes and patterns are extracted for design, and their cultural significance is analyzed. Through semiotics and combination design methods, the structure of traditional tea sets is redesigned to imbue the product with spiritual and cultural value. It is hoped that this design will not only improve the monotonous design environment of the current tea set market but also change people’s lifestyles and perspectives, while effectively promoting regional culture.